Pengaruh E-Commerce Cross Border Terhadap Peningkatan Volume Ekspor Produk Lokal Kota Baubau - Armiyani; La Harjono; Zahwa Nur Syahda (Lembaga Teewan Journal Solutions, 2026)
This study aims to analyze the effect of cross-border e-commerce on increasing the export volume of local products in Baubau City. Digital platforms such as Shopee and TikTok have provided opportunities for local businesses to access international markets more widely. In addition, social media platforms such as Facebook and Instagram support product promotion and improve visibility in the global market. However, local businesses still face limitations in utilizing these digital platforms effectively. This research employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to micro, small, and medium enterprises in Baubau City that utilize digital platforms for export activities. The data were analyzed using linear regression. The results show that cross-border e-commerce positively affects the export volume of local products. The use of e-commerce platforms supported by social media helps expand market reach, increase transactions, and strengthen international marketing activities. Therefore, digital platforms play an important role in improving the export performance of local products in Baubau City.